PENGARUH PEMBELAJARAN FIQIH TERHADAP PELAKSANAAN IBADAH SHALAT PADA SISWA PROGRAM KHUSUS KELAS PERSIAPAN MADRASAH MUALLIMIN MUALLIMAT TAMBAKBERAS JOMBANG - Mohammad Saat Ibnu Waqfin (JoEMS (Journal of Education and Management Studies), 2019)
ABSTRACT The Mualimin Mualimat Bahrul Ulum (MMA BU) Tambakberas preparation class is a class that prepares students who wish to enter MMA BU Tambakberas, but they do not yet have the competence to attend KBM, due to difficult subject matter. Therefore these students must enter the preparatory class. Most prep class students come from elementary school or families who have minimal religious knowledge. In preparatory classes they are educated intensively so that they have within one year the basic competencies and content standards set by the madrasa. With such a background, the researcher is interested in researching, that is, with students who have a background that cannot read Arabic writing, fiqh knowledge is lacking, is it effective learning of jurisprudence in the madrasa. Is there any influence of jurisprudence learning on the implementation of prayer on these students. The purpose of this study was to determine the implementation of jurisprudence learning in the class of mualimin nausea preparation and its effect on the implementation of fardlu prayer for special students of MMA BU preparation classes ". This research is a correlational research with product moment analysis. The research subjects were 49 respondents, using random sampling techniques. Data collection namely the questionnaire and observation instrument. The research data collected was analyzed using descriptive and inferential statistical analysis using the product moment technique. The results show that: There is a positive influence between jurisprudence on the implementation of the prayer of students prayer special programs preparation class MMA BU. Based on the analysis of hypothesis testing with product moments, the results obtained by rxy 0.637 by looking at the table of values ​​of "r" product moment at a significance level of 5% of 0.282 and 1% of 0.365. Thus the rxy or "r" count at the 5% significance level and the 1% significance level is greater than the "r" table (0.637> 0.282), then Ho is rejected and Ha is approved / accepted. Thus at the 5% significance level and the 1% significance level there is a significant positive correlation between the X variable and the Y variable.